Preservice Teachers' Self-Efficacy for Teaching LGBTQ Youth. Issue 4 (2nd October 2021) - Jones, Martin H.; Hershberger, Mary A.; Goodrich, Kristopher M.; Hackel, Tara S.; Love, Abigail
Abstract: The current study examined multiple factors in predicting whether preservice teachers felt self-efficacious for instructing lesbian, gay, bisexual, transgender, and questioning (LGBTQ) students. Among the predictive factors, heterosexist beliefs had the strongest relationship with self-efficacy for teaching LGBTQ students, with participants who reported lower levels of heterosexism demonstrating higher self-efficacy. Contrary to expectations, general teacher self-efficacy was not a strong predictor of self-efficacy for teaching LGBTQ students. Implications for these findings suggest that teacher-training programs should include components that focus on developing preservice teachers' abilities to work with LGBTQ students, including addressing future educators' heterosexist beliefs.